Anatomical Description of the Forelimb Muscles of the Brown-Throated Sloth (Bradypus variegatus) - Alves Diniz, João Augusto Rodrigues; Falcão, Bruna Miniz Rodrigues; Rocha, Ediane Freitas; de Souza, Joyce Galvão; Carreiro, Artur da Nobrega; Medeiros, Gildenos Xavier; de Menezes, Danilo José Ayres (Acta Scientiae Veterinariae, 2018)
Background: Brown-throated sloths are mammals of the order Xenarthra, suborder Pilosa, family Bradypodidae. These folivorous and arboreal animals, which possess a peculiar type of arboreal quadrupedalism, move through the forest canopy by means of suspensory locomotion. On the ground, their extremely slow movements make them easy targets for road accidents, often leading to serious injury or even death. This paper describes the forelimb muscles of the brown-throated sloth (Bradypus variegatus), updating the literature on the subject to help veterinarians in clinical and surgical interventions on this species, and to provide data for comparative animal anatomy. Materials, Methods & Results: Five brown-throated sloths (Bradypus variegatus Schinz, 1825), two adults and three babies were dissected. The animals were donated by the Arruda Câmara Zoo and Botanical Park in João Pessoa, state of Paraíba, Brazil, where they were thawed and fixed in 10% formalin. The sloths’ forelimbs were dissected by lifting and folding over a skin flap to expose, identify and describe the underlying musculature. The dissection revealed the following muscles: supraspinatus, infraspinatus, deltoideus, teres major, subscapularis, coracobrachialis, brachialis, biceps brachii, triceps brachii, anconeus epitrochlearis, dorsoepitrochlearis, brachioradialis, supinator, pronator teres, pronator quadratus, extensor carpi radialis, extensor carpi ulnaris, extensor carpi obliquus, flexor carpi radialis, flexor carpi ulnaris, extensor digitorum communis, extensor digitorum lateralis, palmaris longus, flexor digitorum superficialis, flexor digitorum profundus, extensor indicis longus second finger, extensor indicis brevis second finger, extensor digitorum third finger, abductor digitorum second finger, abductor digitorum third finger, palmaris brevis, and interosseous muscles. Characteristics found in this species revealed differences in the muscular development of the upper forelimb, whose muscles are less developed than those of the lower forelimb, which are visibly more developed with greater muscle density. An interesting feature of this musculature is the presence of three flexor tendons, short and thick, originating from the flexor muscles, which give the hand of the brown-throated sloth a hook-like aspect. Discussion: Our observations indicate that some of the muscles are very similar to those of other animals of this order and also of domestic mammals. However, the most relevant characteristics resemble those of arboreal animals and humans, since the forearm and hand pronation and supination muscles are essential for their arboreal habits. Therefore, all the pronator and supinator muscles of the brown-throated sloth are well developed. Due to the functional adaptations of the species of the family Bradypodidae, the shoulder muscles, especially the deltoideus, are more developed, providing greater support to the shoulder joint, and their origin and insertion assist in faster and easier movements, albeit exerting less force. The group of flexor muscles in this species gives the forearm stronger and more concentrated action than the extensor muscles. This study enabled us not only to produce a more precise description of the muscles of the forelimb of this species but also to update the literature, since there are few relevant studies on the subject and the terms in the literature are outdated and no longer in use. Keywords: sloth, Bradypodidae, morph